Alveolar cytokines and interferon autoantibodies in COVID-19 ARDS - Jonassen, Trine B.; Jørgensen, Sofie E.; Mitchell, Nikki H.; Mogensen, Trine H.; Berg, Ronan M. G.; Ronit, Andreas; Plovsing, Ronni R. (Frontiers in Immunology, 2024)
Background Type I interferon (IFN-I) and IFN autoantibodies play a crucial role in controlling SARS-CoV-2 infection. The levels of these mediators have only rarely been studied in the alveolar compartment in patients with COVID-19 acute respiratory distress syndrome (CARDS) but have not been compared across different ARDS etiologies, and the potential effect of dexamethasone (DXM) on these mediators is not known. Methods We assessed the integrity of the alveolo-capillary membrane, interleukins, type I, II, and III IFNs, and IFN autoantibodies by studying the epithelial lining fluid (ELF) volumes, alveolar concentration of protein, and ELF-corrected concentrations of cytokines in two patient subgroups and controls. Results A total of 16 patients with CARDS (four without and 12 with DXM treatment), eight with non-CARDS, and 15 healthy controls were included. The highest ELF volumes and protein levels were observed in CARDS. Systemic and ELF-corrected alveolar concentrations of interleukin (IL)-6 appeared to be particularly low in patients with CARDS receiving DXM, whereas alveolar levels of IL-8 were high regardless of DXM treatment. Alveolar levels of IFNs were similar between CARDS and non-CARDS patients, and IFNα and IFNω autoantibody levels were higher in patients with CARDS and non-CARDS than in healthy controls. Conclusions Patients with CARDS exhibited greater alveolo-capillary barrier disruption with compartmentalization of IL-8, regardless of DXM treatment, whereas systemic and alveolar levels of IL-6 were lower in the DXM-treated subgroup. IFN-I autoantibodies were higher in the BALF of CARDS patients, independent of DXM, whereas IFN autoantibodies in plasma were similar to those in controls.